THE EFFECT OF PANDEMIC ERA TO STUDENTS’ SOCIAL LITERACY SKILLS - Ella Masita (Sean Institute, 2021)
This paper is aims at understanding on how pandemic might affect students’ competency in literacy specifically in regards to their social literacy skills. The data for this research was collected through the examination of junior high school students’ weekly portfolio reports and observation of their online class interaction in Jambi Municipality. In addition, the discussion also focuses on four dimensions of social literacy. The findings of this research are analysed under four broad categories namely (1) intellectual skills, (2) cooperation skills, (3) social skills, and (4) social attitudes and values. As the conclusion, it is revealed that the pandemic era due to COVID 19 has significantly affect students’ competency in social literacy skills in various aspects.